Navigating Teaching Practice: An Exploration into Prospective Teachers’ Experiences and Reflections - Azeem, Asmaa; Siddiqui, Ghazal Khalid; Ali, Muhammad Shahid Zulfiqar (Journal of Development and Social Sciences, 2024)
The study has been conducted under Interpretivist paradigm while utilizing the Qualitative research approach. Phenomenology method was opted by the researcher(s) to explore the prospective teachers’ experiences and reflections regarding their teaching practice. There were 14 prospective teachers enrolled in their final semester who have been selected with the help of Purposive sampling. The data were collected with the help of a self-developed Semi-structured interview protocol comprising 10 questions. This has been validated while taking the expert’s opinion. The collected data have been analyzed with the help of manual Thematic analysis. Based on the results, it has been concluded that pupil teachers faced confronted the challenges and difficulties that fostered resilience, adaptability, and growth. Through self-reflection and inclusive techniques, their professional development and instructional effectiveness were strengthen. It has been recommended that teacher education institutes ought to emphasize class-room management, Inclusive teaching, lesson planning, and resilience-building.